2004
DOI: 10.1086/421331
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Human TBX4 Gene Cause Small Patella Syndrome

Abstract: Small patella syndrome (SPS) is an autosomal-dominant skeletal dysplasia characterized by patellar aplasia or hypoplasia and by anomalies of the pelvis and feet, including disrupted ossification of the ischia and inferior pubic rami. We identified an SPS critical region of 5.6 cM on chromosome 17q22 by haplotype analysis. Putative loss-of-function mutations were found in a positional gene encoding T-box protein 4 (TBX4) in six families with SPS. TBX4 encodes a transcription factor with a strongly conserved DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
147
0
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(156 citation statements)
references
References 36 publications
0
147
0
5
Order By: Relevance
“…147891) and Holt-Oram syndrome (HOS; OMIM no. 142900), respectively (Basson et al, 1997;Li et al, 1997;Bongers et al, 2004). HOS is a dominant disorder affecting the heart and upper limbs.…”
Section: Tbx Genes Establish the Fgf Signalling Loop In The Nascent Lmentioning
confidence: 99%
“…147891) and Holt-Oram syndrome (HOS; OMIM no. 142900), respectively (Basson et al, 1997;Li et al, 1997;Bongers et al, 2004). HOS is a dominant disorder affecting the heart and upper limbs.…”
Section: Tbx Genes Establish the Fgf Signalling Loop In The Nascent Lmentioning
confidence: 99%
“…Because these differences were already clear at E11.5 and ablation of Tbx4 after E11.5 led to no additional phenotype, the early loss of limb core tissue was almost certainly the origin of the skeletal malformations observed at E14.5. This suggests that the limb malformations seen in human heterozygous mutations of TBX4 (Bongers et al, 2004), which cause mild malformation of pelvis, patella size and toe placement (Small Pateela Syndrome, OMIM 147891), are determined in early development rather than during later limb outgrowth. Gene ablation and lineage tracing has shown that digit I is Shhindependent, and digit II is induced by neighboring Shh signaling, while digits III, IV and V arise from tissue that once expressed Shh (Harfe et al, 2004).…”
Section: Hindlimb Formation Requirements For Tbx4mentioning
confidence: 99%
“…Several T-box genes are expressed in the limb (Naiche et al, 2005), and heterozygous mutations in TBX3, TBX4 and TBX5 cause limb defects in humans (Bamshad et al, 1997;Basson et al, 1997;Bongers et al, 2004). In mouse, all of the Tbx2 subfamily (Tbx2, Tbx3, Tbx4 and Tbx5) have been shown to play roles in limb development (Agarwal et al, 2003;Davenport et al, 2003;Harrelson et al, 2004;Naiche and Papaioannou, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Küçük patella sendromu otozomal dominant geçişli bir sorundur. [21] Patellar hipoplazi veya aplazi, iskiyopubik birleşkenin iki taraflı gecikmiş veya oluşmamış ossifikasyon merkezi ve infra-asetabuler balta şekilli çentikler ile karakterizedir (Şekil 3). Küçük patella sendromuna 1. ve 2. ayak parmak arasının normalden geniş olması, ayakta kısa 4. ve 5. metatarsal kemikler ve pes planus eşlik edebilir.…”
Section: Küçük Patella Sendromuunclassified
“…Bazı olgularda ise, talus boynunda hipertrofi, tarsal koalisyon, skapulanın anormal şekli, kısa 4. ve 5. metakarplar, koksa vara veya valga, genu valgum, dar ve uzun femur boyunları ve hipoplastik trokanter minörler bildirilmiştir. [20,21] …”
Section: Küçük Patella Sendromuunclassified